Manajemen Pengembangan Keprofesian Berkelanjutan (PKB) Kepala Sekolah Dasar (SD) dalam pengelolaan hasil supervisi akademik di SD Negeri Kemirirejo 3 Kecamatan Magelang Selatan Kota Magelang: Manajemen, kompetensi profesional,supervisi akademik - Esti Hariyanti (Universitas Sarjanawiyata Tamansiswa, 2022)
Esti Hariyanti, Management of continuing professional development (CPD) Principal of elementary school (SD) In academic supervision management at SD Negeri Kemirirejo 3 District Magelang Tengah, Magelang City. Thesis. Yogyakarta: Educational Management Study Program, Postgraduate Directorate, Universitas Sarjanawiyata Tamansiswa. Research objective include: First understanding PKB management of SD principal in the manage of academic supervision result in SD Negeri Kemirirejo 3 District Magelang Tengah Magelang City; second understand the supporting factors, constraints and solutions that affect the management of the PKB Principal in managing the results of academic supervision ; third understanding the results of the PKB management of the SD Principal in managing the results of academic supervision at SD Negeri Kemirirejo 3 District Magelang Tengah Magelang City. This type of research is using a descriptive qualitative research design. Data collection techniques in this research include interviews, observation, and documentation. This research conducted in SD Negeri Kemirirejo 3 District Magelang Tengah Magelang City. The data sources of this research were 1 principal, 16 teachers and 1 supervisor. The data analysis technique used descriptive qualitative analysis which included data collection, data reduction, data presentation, and drawing conclusions. The results of the research and discussion show that the PKB Management Program for the Principal of SD in managing the results of academic supervision has been carried out well in SD Negeri Kemirirejo 3 namely: First PKB consists of: Self-Development, Scientific Research, and Innovative Work. Its management is through the management functions of Planning, Organizing, Implementation, and monitoring and Evaluation; second supporting factors, inhibiting factors and solutions were also found from the implementation of PKB Principal Management in managing the results of academic supervision. The supporting factors for the PKB program are mainly the support of school residents and supervisors, dedication, motivation of the Principal, sources of funds in the RKAS and available infrastructure. The inhibiting factors are different teacher competencies, limited funding sources, the same activity time. Solutions that are implemented by rescheduling activities, coordination, and self-funding the use of the obtained teacher professional allowance; third the results of the PKB program are: teacher performance is increasing, learning services are more innovative with various learning media, there is 1 CKS balloon, 3 people who continue to study Masters, modules, best practices, PTS, competency improvement certificates, teacher achievement championships, SKP according to target, and promotion according to target. Keywords: Management, professional competence, academic supervision.